Improving Graduate Quality and Public Satisfaction through Internal Quality Assurance - Habibi, Riki; Badrudin, Badrudin; Thoha, Anis Malik; Arifin, Bambang Samsul; Erihadiana, Mohamad (JURNAL AL-TANZIM, 2025)
This study analyzes the implementation of Internal Quality Assurance Standards (SPMI) in pesantren to identify its impact on graduate quality and community satisfaction. The research design used a mixed-method sequential explanatory approach. The quantitative phase involved 457 respondents and was analyzed using SmartPLS to examine the influence of SPMI on graduate quality and community satisfaction. The qualitative phase was conducted through in-depth interviews with kiai (Islamic scholars), teachers, and alums to interpret the quantitative results and explore the value-based quality practices of pesantren. The quantitative results showed that SPMI had a more substantial influence on graduate quality (β = 0.72; R² = 0.52), while the most dominant influence on community satisfaction was found in pesantren (β = 0.70; R² = 0.51). Qualitative findings confirmed these results by identifying integrative curriculum practices, spiritual-moral guidance (ta'dib), life skills development, and the social contributions of pesantren. These findings confirm that SPMI in pesantren is not merely an administrative instrument but a systemic strategy that integrates academic, spiritual, moral, and social dimensions. This study provides new insights into variations in SPMI implementation in pesantren and offers a quality assurance model that is contextual and aligned with Islamic scientific traditions.